Organ injuries due to thoracic trauma : Diagnostics, clinical importance and treatment principles - Schreiner, Waldemar; Castellanos, I.; Dudek, Wojciech; Sirbu, Horia (Unfallchirurg, 2018)
Thoracic trauma can be a life-threatening condition due to the involvement of vital organs, such as the heart, lungs, tracheobronchial tree and the great vessels. A coordinated interdisciplinary management is vital for the survival of the injured person. Modern diagnostic procedures provide an essential basis for the surgical treatment of patients. Surgical treatment principles include insertion of chest drainage, emergency thoracotomy, complex bronchoplastic and vascular reconstructive techniques and cardiac surgical maneuvers. For this reason highly complex surgical procedures are available, which can be effectively and specifically integrated into an interdisciplinary concept. In this review, the most frequent and prognostically relevant conditions, the indicated diagnostics and their significance as well as the surgical treatment principles, are comprehensively presented under consideration of the clinical situation.
EVALuna2:35730